"A duet, in which your goal is to kill your partner": Aggressive Empathy and Visceral Reading in Fantasy Action Scenes. Issue 1 (1st April 2023) - Oliver, Matthew
Abstract : While literary criticism often treats fantasy action scenes as cognitively empty and politically regressive, close analysis of the use of perspective in fantasy action reveals that the experiential, visceral reading invited by such action actually subverts some of literary criticism's core narratives about itself. Perspective in action scenes troubles both the emphasis on empathy as a literary value and the critique of literature as the enforcement of a disciplinary regime. Through its use of "aggressive empathy, " successful combat entails seeing through the eyes of one's opponent, yet matching features between self and other does not exclude the attempt to violently dominate the other. Engaging in theoretical discussion with Rita Felski and Martha Nussbaum, Jacques Rancière and D. A. Miller, and Jacques Derrida and Emmanuel Levinas, and analyzing characteristic action scenes by Robert E. Howard, Katherine Kurtz, Ian C. Esslemont, Karen Miller, and others illustrates the limitations on both literary empathy and literary surveillance.